Rancang Bangun Jaket Multifungsi Sebagai Pelindung Badan Dan Charger Baterai Handphone - Romeo Saputra; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
With rapid growth of technology, cellphone is very important for human being. The need of cellphone is to connect our friends and family and for daily work. But everyone will have an awkward time is battery died in the hot sun. Then we cannot to connect our friends and family. If we have a sunshade can receive the solar energy to charge our phone. The solar-powered jacket has an embedded flexible solar panel, which can absorb the solar energy and convert heat energy to electrical energy. We will have a converter circuit that will convert the supply to a suitable voltage for cellphone charging. This jacket is a convenient product, easy to carry, light in weight, and it is green environment products.Keywords :Panel Surya Fleksibel, Dc to dc Konverter dan IC L7805CV , USB Output dan Penyimpan Daya